2007
DOI: 10.1111/j.1440-1746.2006.04730.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial of transnasal versus peroral endoscopy using an ultrathin videoendoscope in unsedated patients

Abstract: For unsedated endoscopy using an ultrathin videoendoscope, transnasal EGD is well tolerated and considerably reduces patient discomfort compared with peroral EGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 20 publications
5
64
0
Order By: Relevance
“…Previous studies have reported that the diagnostic accuracy of transnasal EGD is equivalent to that of standard transoral EGD for the detection of esophagogastric lesions, including gastric cancer [23][24][25][26][27][28][29][30] . However, despite recent advances in endoscopic technologies, small-diameter endoscopes used for transnasal EGD still show disadvantages when compared to standard endoscopes, due to lower luminous intensity, lower resolution of endoscopic images, a narrow field of view, low maneuverability and low biopsy performance, all of which are attributable to the small diameter of the endoscope [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the diagnostic accuracy of transnasal EGD is equivalent to that of standard transoral EGD for the detection of esophagogastric lesions, including gastric cancer [23][24][25][26][27][28][29][30] . However, despite recent advances in endoscopic technologies, small-diameter endoscopes used for transnasal EGD still show disadvantages when compared to standard endoscopes, due to lower luminous intensity, lower resolution of endoscopic images, a narrow field of view, low maneuverability and low biopsy performance, all of which are attributable to the small diameter of the endoscope [31] .…”
Section: Discussionmentioning
confidence: 99%
“…But both of the procedures have to change the tube from mouth to nose in the end, which aggravate the patient's discomfort and prolong the operation time. Transnasal gastroscopy with an outer diameter of 5.1-5.9 mm has been developed and used frequently for more than 10 years, which has been reported to be safer and more tolerable than traditional transoral gastroscopy (17,18). Compared with using traditional transoral gastroscope, nasoendoscopical placement method does not have to change the tube from mouth to nose in the end of the procedure, which shows advantage as a more successful technique for tube placement than others (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Unsedated transoral EGD is well known to increase BP and PR, with an increased cardiopulmonary work load [2,[4][5][6] . Recently, small-caliber endoscopes have been developed and used for EGD with the transnasal route.…”
Section: Discussionmentioning
confidence: 99%
“…Small-caliber endoscopy of the upper gastrointestinal tract was developed and for transnasal esophagogastro duodenoscopy (EGD) and has been used frequently in the past decade [1][2][3][4] . Transnasal small-caliber EGD has improved the safety of the endoscopic examination, and has fewer adverse effects on cardiopulmonary function [5][6][7][8][9][10] and autonomic nerve function [11] , compared with transoral conventional EGD.…”
Section: Introductionmentioning
confidence: 99%